PCRRT Expert Committee ICONIC Position Paper on Prescribing Kidney Replacement Therapy in Critically Sick Children With Acute Liver Failure - Raina, Rupesh; Sethi, Sidharth K.; Filler, Guido; Menon, Shina; Mittal, Aliza; Khooblall, Amrit; Khooblall, Prajit; Chakraborty, Ronith; Adnani, Harsha; Vijayvargiya, Nina; Teo, Sharon; Bhatt, Girish; et al. (Frontiers in Pediatrics, 2022)
Management of acute liver failure (ALF) and acute on chronic liver failure (ACLF) in the pediatric population can be challenging. Kidney manifestations of liver failure, such as hepatorenal syndrome (HRS) and acute kidney injury (AKI), are increasingly prevalent and may portend a poor prognosis. The overall incidence of AKI in children with ALF has not been well established, partially due to the difficulty of precisely estimating kidney function in these patients. The true incidence of AKI in pediatric patients may still be underestimated due to decreased creatinine production in patients with advanced liver dysfunction and those with critical conditions including shock and cardiovascular compromise with poor kidney perfusion. Current treatment for kidney dysfunction secondary to liver failure include conservative management, intravenous fluids, and kidney replacement therapy (KRT). Despite the paucity of evidence-based recommendations concerning the application of KRT in children with kidney dysfunction in the setting of ALF, expert clinical opinions have been evaluated regarding the optimal modalities and timing of KRT, optimal vascular access points, dialysis/replacement solutions, blood and dialysate flow rates and dialysis dose, and anticoagulation methods.